Partial androgen insensitivity syndrome: Incidentally diagnosed in an adolescent - A J Aparna; I Riaz; V H Sankar; Devakumar Vasanthiamma Krishnannair (Wolters Kluwer Medknow Publications, 2023)
Background: Androgen insensitivity syndrome is an X-linked genetic disease characterized by resistance to the actions of androgen in an individual with 46, XY karyotype. It is one of the most common causes of Disorders of sex development (DSD). Clinical Description: A 10-year-7-month-old child, reared as female, was incidentally detected with minor virilization of external genitalia. She had achieved thelarche and adrenarche with a Prader Stage 2. Management and Outcome: Routine investigations showed normal hemogram and kidney and liver functions, as also normal values of serum electrolytes. Ultrasonogram showed the absence of Mullerian structures and the presence of prostate- and testis-like structures. Karyotyping showed 46, XY. There were grossly elevated levels of testosterone and dihydrotestosterone, as well as raised follicle-stimulating hormone and luteinizing hormone levels. Diagnostic laparoscopy showed inguinal testis-like structures and biopsy from the same confirmed testicular tissue. Parents were counseled regarding the prognosis, need for gonadectomy, and hormone replacement. Conclusion: Our case creates awareness regarding the importance of early identification of minor virilizing features in a child, so as to avoid late revelation of an underlying DSD leading to undue anxiety and psychological trauma to parents and child.